Structure Design and Kinematics Parameter Calibration of Master Manipulator - Sang Hongqiang; An Da; Zhang Xinjian (Jixie chuandong)
To better improve the performance of master manipulator, reduce the fatigue caused by the gravity of the mechanism during operation, and improve the positioning accuracy, a master manipulator with seven degrees of freedom is designed. The boom mechanism is a parallelogram mechanism that provides front & rear and left & right degrees of freedom (DOFs). The arm mechanism provides up & down degree of freedom (DOF). The wrist mechanism provides pitch and yaw DOFs. The end operator mechanism provides roll, and opening & closing DOFs. On the basis of the structure design of the master manipulator, the kinematics model and error model of the master manipulator are established by using screw theory to improve the positioning accuracy. The kinematics parameters are identified by using the least squares method. The kinematics calibration experiment is carried out. The results show that the maximum position error of the master manipulator is improved by 67.43% after kinematics parameters calibration.